DEVELOPMENT WORKSHEET PHYSICS TEMPERATURE MATERIAL AND KALOR WITH DISCOVERY LEARNING MODEL BASED ON METAKOGNITIF APPROACH - yuda seta mahendra; Chandra Ertikanto; Undang Rosidin (Jurnal Pendidikan Fisika, 2018)
AbstractMetacognitive approach is a very closely related approach to human knowledge. One of the things that must be considered by teachers in knowing how metacognitive work is by giving instructional materials in the form of LKS (Worksheet) with metacognitive approach. Based on the background of the problem of the objectives of this study to develop LKS Physics on the material temperature and heat calorically valid, practical, and effective with discovery-based learning model metacognitive approach. This type of research is research and development (R & D). The research procedure using Sugiyono development model adopted from Borg N Gall model. The subject of this research is 47 students of XI class MIA, MA Bustanul Ulum Central Lampung. The results of this research and development are (1) the validity of the LKS meet the criteria is quite valid in terms of design aspects and material aspects; (2) the practicality of LKS meet the criteria both in terms of one-on-one test and questionnaire responses students on aspects of attractiveness, aspects of ease, and aspects of usefulness in good category; (3) the effectiveness of LKS in terms of student learning outcomes meet the data of the postes result showed that the average score of the experimental class is 75, while the control class is 68.